Fatty acid composition of mid-trimester amniotic fluid in women of different ethnicities - Witkin, Steven Sol [UNESP]; Skupski, Daniel; Herway, Catherine; Rudge, Marilza Vieira Cunha [UNESP]; Saito, Felipe [UNESP]; Harris, Mary (Informa Healthcare, 2012)
Objective: To determine whether the fatty acid composition of mid-trimester amniotic fluid differs by ethnicity and pregnancy outcome. Methods: Fatty acid composition was analyzed by gas chromatography in 198 women undergoing amniocentesis at 15-19 weeks gestation. Cytokine levels were determined by ELISA in a subgroup of 52 subjects. Results: The major fatty acids detected were palmitic acid (31.8%) and stearic acid (31.5%). The n-6 polyunsaturated fatty acids (PUFA), linoleic acid (LA, 18: 2) and arachidonic acid (AA, 20: 4), were 11.3%, while the n-3 PUFA fatty acids, alpha linolenic acid (ALA, 18: 3) and docosahexaenoic acid (DHA, 22: 6), were 3.8% of the total. Palmitic acid was a higher percentage in Asians (40.5%) and Whites (34.5%) than in Blacks (22.2%) and Hispanics (23.7%) (p <= 0.0012). Oleic acid (18:1 n-9) was a higher percentage in Blacks (12.2%) and Hispanics (12.1%) than in Whites (9.2%) or Asians (7.5%) (<= 0.0002). LA and AA were higher in Blacks (9.0%, 5.4%) and Hispanics (8.6%, 4.1%) than in Whites (6.1%, 3.7%) and Asians (5.5%, 2.9%) (p <= 0.0002). DHA did not differ among the ethnic groups or according to pregnancy outcome. A reduced palmitic acid percentage was identified in the six women with preeclampsia (p = 0.0233). Tumor necrosis factor-alpha levels were inversely proportional to the palmitic acid percentage (p = 0.0275) and positively associated with the percentages of stearic (18:0) (p = 0.0132) and oleic (p = 0.0290) acids. Conclusions: Amniotic fluid fatty acid composition differed among the ethnic groups and may influence inflammatory mediator production and susceptibility to preeclampsia.
Keywords: amniotic fluid; fatty acids; preeclampsia; pregnancy outcome; tumor necrosis factor-alpha